Effect of Patients' Education on Their Performance and Outcomes Regarding Lumbar Disk Herniation - Heba A. Ali; Safaa M. Hamed (Evidence-Based Nursing Research)
Context: Lumbar disc herniation is a common condition in adults and can impose a heavy burden on both the individual and society. Aim: The present study aimed to evaluate the effect of patients' education on their performance and outcomes regarding lumbar disk herniation. Methods: Quasi-experimental design used to achieve aim in this study. The study conducted at the orthopedic outpatient clinic at Benha University Hospital. Purposive sample of 60 patients of both genders who aged from (18-60 years old) included in the study. Patients who were attending surgical operation regarding lumbar disk herniation excluded. Three tools used to collect the study data. These are structured interview questionnaire regarding the patients' demographic characteristics, medical data, and patient's knowledge regarding lumbar disk herniation, observational checklist for patient's practice regarding lumbar disk herniation exercises, and modified Oswestry low back pain & disability scale Result: There was a statistically significant improvement in the total level of patient's knowledge, practices & outcomes immediately post and three months post-program implementation. Also, there was a significant statistical correlation between patients' knowledge and pain disability scale three months post-program implementation. Conclusion: The results of the study conclude that the educational program was effective and resulted in a significant improvement in patient's knowledge, practice, and outcomes regarding lumbar disk herniation. The study suggested equips the orthopedic department with simple illustrated guidelines protocol covering lumbar disc herniation practices, knowledge; reapply this research on a more substantial probability sample acquired from different geographical areas in Egypt for generalization.